Os hospitais e a assistência aos doentes em Coruche no século XIX e princípio do século XX - Correia, Ana (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
Until the end of the 19th century the Portuguese villages of Coruche and Erra had two hospitals, which were managed by the local Misericórdias. The hospital of Coruche was the main healthcare facility and the only one that remained after 1883, when the failing brotherhood of Erra was assimilated into the Misericórdia of Coruche, and its hospital became extinct.. In this paper we describe the services provided by the hospitals during the 19th century and first decade of the 20th century. We analyzed the share of expenditure of the hospital in the budget of the brotherhood of Coruche, its medical staff, including their technical capabilities. Furthermore, the users of the hospitals are quantified and described. The fragility of the Hospital of Erra is also proved, as well as of the Misericórida of the same village, reflected in the weak assistance provided and on the low number of patients that it could receive.